KERANGKA KEBIJAKAN PENDIDIKAN ISLAM DI INDONESIA: PRINSIP DASAR DAN REGULASI - Muh Agus Syahnginata Surya; Sabran (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This article examines the framework of Islamic education policy in Indonesia, focusing on the integration of fundamental Islamic principles into national education regulations. This study aims to analyze the extent to which fundamental values such as tawhid and akhlak are accommodated in public policy, particularly from the perspective of Law No. 20 of 2003 on the National Education System and Law No. 18 of 2019 on Pesantren. The research method employed is qualitative, utilizing a literature review (library research) design. Data were collected through documentation and textual analysis of regulatory documents and academic literature from the 2020–2026 period, which were then analyzed using content analysis techniques. The research findings indicate that although the legal framework has provided formal recognition of Islamic education, its implementation still faces structural obstacles such as institutional dualism and regulatory fragmentation. A critical analysis concludes that digital transformation and regulatory harmonization are key strategies for enhancing the relevance of Islamic education in the Society 5.0 era. These findings contribute to the development of educational policies that are more integrative and adaptive to global challenges.